1993
DOI: 10.1002/eji.1830230325
|View full text |Cite
|
Sign up to set email alerts
|

Soluble T cell receptor‐like properties of an HLA‐B35‐specific monoclonal antibody (TÜ165)

Abstract: A mouse monoclonal antibody of IgM class (TU165) was produced using Epstein-Barr virus (EBV)-infected mutant cells derived from the human BJAB-B95.8.6 cell line as immunogen. Binding studies with several HLA deletion mutant cell lines indicated that TU165 recognized the HLA-B35 molecule. In a panel of 89 EBV-transformed lymphoblastoid cell lines, all HLA-B35+ cells (n = 24) reacted with TU165 while all but two HLA-B35- lines (n = 65) were unreactive (r = 0.95). Surprisingly, peripheral blood lymphocytes of HLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…The first of the mAbs, W6/32HL, is a well-known antibody directed at a non-polymorphic framework determinant of all HLA class I molecules that are complexed to β 2 -m ( Barnstable et al 1978). The second is TÜ149 (Uchanska-Ziegler et al 1993), which has a reactivity for HLA-B, -C, and some -A molecules that are complexed with β 2 -m. The third antibody, HCA2, which was originally described by Stam et al (1990) as detecting HLA-A heavy chains, has recently been further characterized (Grandea et al 1995). To confirm its reactivity with HLA-G heavy chains, in addition to HLA-A heavy chains, we determined the reaction pattern of HCA2 by using onedimensional isoelectric focusing (IEF) of lysates from LG-2, JAR, and JEG-3 cells, followed by Western blotting.…”
Section: Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The first of the mAbs, W6/32HL, is a well-known antibody directed at a non-polymorphic framework determinant of all HLA class I molecules that are complexed to β 2 -m ( Barnstable et al 1978). The second is TÜ149 (Uchanska-Ziegler et al 1993), which has a reactivity for HLA-B, -C, and some -A molecules that are complexed with β 2 -m. The third antibody, HCA2, which was originally described by Stam et al (1990) as detecting HLA-A heavy chains, has recently been further characterized (Grandea et al 1995). To confirm its reactivity with HLA-G heavy chains, in addition to HLA-A heavy chains, we determined the reaction pattern of HCA2 by using onedimensional isoelectric focusing (IEF) of lysates from LG-2, JAR, and JEG-3 cells, followed by Western blotting.…”
Section: Antibodiesmentioning
confidence: 99%
“…Ag4-1 myeloma cells (Köhler et al1976;Uchanska-Ziegler et al 1993) with spleen cells from a female BALB/c mouse immunized with phytohemagglutinin-activated T cells from a healthy individual; differential screening was performed on a panel of hematopoietic cell lines. TÜ155 was determined to be an IgM and apparently reacts only with HLA-A molecules.…”
Section: Antibodiesmentioning
confidence: 99%
“…The unexpected high frequency of these antibodies and the ability to isolate several different antibodies directed to either complex is even more surprising in view of previous reports, in which the use of immunized or naive phage libraries resulted in only a single antibody clone [28,29,[46][47][48][49][50][51][52][53][54][55]. It would have been possible that one particular antibody family or antibody V gene segment would have an intrinsic propensity to bind HLA-A2 molecules, and that the high frequency could be explained by a high abundance of such antibodies in the nonimmune library.…”
Section: Strategies To Generate Antibodies With Tcr-like Specificitiesmentioning
confidence: 84%
“…Antibodies with the MHC-restricted specificity of T-cells are rare and have been difficult to generate by conventional hybridoma techniques because B-cells are not educated to be self-MHC restricted [24][25][26][27]52,54]. TCRs recognize intracellularly processed linear peptide antigens in the context of MHC molecules.…”
Section: Antibodies With Mhc-restricted Peptide-specific Binding: Tcmentioning
confidence: 99%
“…Some of these reagents were Abs that were generated in an MHC-restricted fashion against tumor Ags (62,63) or against the H-Y Ag (64). Other groups have demonstrated that particular mAbs recognize only a subset of the MHC molecules to which they were directed, and have suggested that such restricted reactivity was due to peptide specificity (65)(66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%